2009
DOI: 10.3109/10408440903307333
|View full text |Cite
|
Sign up to set email alerts
|

Fungal spores: A critical review of the toxicological and epidemiological evidence as a basis for occupational exposure limit setting

Abstract: Fungal spores are ubiquitous in the environment. However, exposure levels in workplaces where mouldy materials are handled are much higher than in common indoor and outdoor environments. Spores of all tested species induced inflammation in experimental studies. The response to mycotoxin-producing and pathogenic species was much stronger. In animal studies, nonallergic responses dominated after a single dose. Allergic responses also occurred, especially to mycotoxin-producing and pathogenic species, and after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(142 citation statements)
references
References 190 publications
6
133
0
3
Order By: Relevance
“…Their size ranges usually from 1 to 10 µm with variations even among the same species. Besides fungal spores, fragments of mycellium may also be released in the air with sizes even smaller than fungal spores (8)(9)(10). Inhalation of these particles represents a threat to human health due to possible deposition in the lower respiratory system and interactions with lung tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their size ranges usually from 1 to 10 µm with variations even among the same species. Besides fungal spores, fragments of mycellium may also be released in the air with sizes even smaller than fungal spores (8)(9)(10). Inhalation of these particles represents a threat to human health due to possible deposition in the lower respiratory system and interactions with lung tissue.…”
mentioning
confidence: 99%
“…It has been suggested that occupational concentrations of airborne fungi above 10 4 cfu m -3 should be considered a health hazard in non-sensitized subjects, although this does not mean that such a working environment will necessarily lead to any respiratory symptoms (9)(10)(11)(12)(13). Considering the limited number of studies addressed at the fungal burden in occupational environments and urban homes in our country, the aim of the present study was to investigate the composition and concentration of aeromycota in industrial and residential environments in Zagreb, Croatia, for which purpose measurements were performed in a grain mill, an apartment and a basement.…”
mentioning
confidence: 99%
“…Thermophilic actinomycetes are bacteria that thrive at higher temperatures and cause hypersensitivity pneumonitis (also referred to as extrinsic allergic alveolitis) [Eduard 2009]. Hypersensitivity pneumonitis is an immunologically-mediated, granulomatous lung disease caused by repeated inhalation and sensitization to various organic agents Discussion (continueD) including microbial agents [Girard et al 2004].…”
Section: Microbial Contamination -Carpet and Ventilation Supply Ductsmentioning
confidence: 99%
“…As outdoor air is often filtered before entering in the ventilation system and fungi settle due to lower air velocities in buildings than outdoors, common indoor fungal levels are expected to be lower than levels in outdoor air [1]. However, in hospital settings there are diverse possible sources of fungal contamination including ventilation or air-conditioning systems, decaying organic material, dust ornamental plants, food, water and, particularly, building works in and around hospitals [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Health hazards may differ across species because fungi may produce different allergens and mycotoxins, and some species can infect humans [1]. Exposure effects to fungi are dependent on the species present, the metabolic products produced, concentration and duration of the exposure, and also individual susceptibility [2].…”
Section: Introductionmentioning
confidence: 99%